Professional burnout among hospital nursing and administrative staff and the tendency of nurses to move to administrative posts - Grigoropoulou, M.; Patsaki, A.; Katsari, B.; Sarafis, Pavlos; Bamidis, P.; Varaklioti, A.; Domeyer, F. (My University, 2018)
OBJECTIVE To measure the prevalence of burnout among hospital nursing and administrative staff and to explore its possible correlation with demographic and work factors and its impact on health-related quality of life (HRQoL). In addition, the possible intention of nurses to change to a management position was investigated. METHOD The study sample consisted of 292 nursing and administrative staff of two hospitals, one in the capital city and one in a provincial town. Data collection was by self-completion of questionnaires: Maslach’s Burnout Inventory (MBI), the Short Form Questionnaire (SF-36) for assessment of HRQoL, along with two questions constructed by the researchers. Data analysis was performed using the Statistical Package for Social Sciences (SPSS) v. 19.0. RESULTS The respondents expressed a high rate of burnout: 26.4% based on emotional exhaustion, 42.5% based on lack of personal accomplishment and 34.9% based on depersonalization. Linear regression analysis showed that emotional exhaustion has an effect on all the dimensions of QoL measured by SF-36 (all p≤0.001). The dimension of depersonalization had an impact on physical function (p=0.011) and emotional role (p<0.001), and that of personal achievement affected the score on the vitality scale (p=0.010). No clear intention of nurses to move to administrative posts was identified. CONCLUSIONS A high rate of burnout was recorded in both the nursing and the administrative staff of the two hospitals studied (capital city and provincial). Further research is needed to better understand the phenomenon of burnout among hospital staff and to find ways of mitigating and preventing it in this particularly sensitive health setting.
Η επαγγελματική εξουθένωση νοσηλευτικού και διοικητικού προσωπικού και διερεύνηση της τάσης μεταπήδησης των νοσηλευτών σε διοικητικές θέσεις
Keywords: Demographic characteristics; Intention to change; Nursing and administrative staff; Professional burnout; Work quality of life